Non-linear inelastic analysis of steel arches at elevated temperatures - Heidarpour, Amin; Abdul Azim, Abdullah; Bradford, Mark A. (Elsevier Ltd., 2009)
An innovative non-discretisation mechanical-based method is developed in this paper to analyse a steel arch at elevated temperatures so that its behaviour can be quantified. The steel arch has a generic but singly-symmetric cross-section with elastic and plastic parts,and it is subjected to an arbitrary thermal profile which varies along the length of the arch as well as through the depth of the cross-section. The effects of geometric and material non-linearity as well as potential catenary action which can occur at high temperatures are taken into account in the formulation.The efficiency and accuracy of the generic model developed is demonstrated by a comparison with a finite element model undertaken using ABAQUS. The proposed method is then utilised to elucidate some significant factors,such as the magnitude of the temperature at bottom fibre of the cross-section as well as the ratio of the temperature at the top fibre to that at the bottom fibre, on the response of a steel arch member during fire loading. The proposed model provides a computationally superior formulation to that of commercial finite element packages,and forms a platform which can be used for structural steel arch design and evaluation in the development of codified approaches to fire design on a performance basis.